Mixed-member proportional electoral systems – the best of both worlds?. Issue 1 (2nd January 2019) - Linhart, Eric; Raabe, Johannes; Statsch, Patrick
ABSTRACT: Mixed electoral systems are often associated with the hope of combining proportional election outcomes with a concentrated party system, and thus achieving the best of both worlds in electoral system design. It is especially the mixed-member proportional (MMP) variant that has retained a good reputation in this regard. Via a comparative analysis, we analyze whether or not the general praise for MMP systems is corroborated empirically. Our results show that the performance of MMP systems is heavily influenced by technical details, and elections conducted under MMP vary broadly with regard to possible proportionality–concentration combinations.